Introducing Self –Efficacy Beliefs: An Unexploited Construct in the Algerian Academic Setting - SAKRAOUI, Amel (Journal of Human Sciences, 2010)
Self-efficacy is currently one of the most popular belief systems in educational psychology. It is an attribute that should be nurtured and enhanced because it contributes tremendously to positive feelings of accomplishment and well-being. This paper attempts basically at introducing the reader to the construct of self-efficacy through tackling issues that are closely relevant to it namely, its nature (structure), theoretical background, sources of development and effects, its popularity and assessment. Investigating both the subtle and complex net of conceptions and judgments students develop about their personal competence in the context of learning English as a foreign language might constitute a promising avenue of research for teachers aiming at getting a clearer understanding about the causes underlying the level of their students’ attainment in the language.